Perspective on Improving Environmental Monitoring of Biothreats - Dunbar, John; Pillai, Segaran; Wunschel, David; Dickens, Michael; Morse, Stephen A.; Franz, David; Bartko, Andrew; Challacombe, Jean; Persons, Timothy; Hughes, Molly A.; Blanke, Steve R.; Holland, Robin; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
For more than a decade, the United States has performed environmental monitoring by collecting and analyzing air samples to detect a possible biological attack with a handful of biological threat agents (BTAs). This effort has faced numerous technical challenges including timeliness, sampling efficiency, sensitivity, specificity, and robustness. The cost of city-wide environmental monitoring using conventional technology has also been a challenge. After assessing the objectives and current efficacy of environmental monitoring, a large group of scientists with expertise in bioterrorism defense met and identified operational and technological changes that could enhance its efficacy and cost-effectiveness, thus enhancing its value. The highest priority operational change identified by these experts was to abandon the concept of city-wide environmental monitoring because the operational costs were too high and its value was compromised by low detection sensitivity. Instead, the focus should primarily be on indoor monitoring and secondarily on special-event monitoring because objectives are tractable and these operational settings are aligned with risk assessments. The highest priority technological change is the development of a reagent-less, real-time sensor that can identify a potential airborne release and trigger secondary tests of greater sensitivity and specificity for occasional samples of interest. This technological change could be transformative with the potential to greatly reduce operational costs and thereby creating the opportunity to expand the scope and effectiveness of environmental monitoring.